Kegiatan Pengabdian Masyarakat: Penyuluhan tentang Pencegahan Penyakit oleh Perawat Komunitas di Masyarakat di Wilayah Desa Bunda Kab. Mamuju Sulbar Tahun 2024 - Musdalifah, Musdalifah (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Community service activities are one form of implementation of community nursing knowledge to support public health improvement through promotive and preventive approaches. Bunda Village, Mamuju Regency, West Sulawesi, is an area with low public awareness of clean and healthy living behaviors. This impacts the high incidence of infectious and non-communicable diseases. The objective of this activity was to increase public knowledge about disease prevention through health education conducted by community nurses. The activity methods included lectures, interactive discussions, and the distribution of educational leaflets. The results of the activity showed an increase in public understanding. Before the education, only 52% of participants understood the basic concepts of disease prevention, while after the education, this increased to 85%. This activity is expected to strengthen public awareness to implement clean and healthy living behaviors in their daily lives.